Diversity and biomass dynamics of unicellular marine fungi during a spring phytoplankton bloom. (3rd December 2020) - Priest, Taylor; Fuchs, Bernhard; Amann, Rudolf; Reich, Marlis
Summary: Microbial communities have important functions during spring phytoplankton blooms, regulating bloom dynamics and processing organic matter. Despite extensive research into such processes, an in‐depth assessment of the fungal component is missing, especially for the smaller size fractions. We investigated the dynamics of unicellular mycoplankton during a spring phytoplankton bloom in the North Sea by 18S rRNA gene tag sequencing and a modified CARD‐FISH protocol. Visualization and enumeration of dominant taxa revealed unique cell count patterns that varied considerably over short time scales. The Rozellomycota sensu lato (s.l.) reached a maximum of 10 5 cells L −1, being comparable to freshwater counts. The abundance of Dikarya surpassed previous values by two orders of magnitude (10 5 cells L −1 ) and the corresponding biomass (maximum of 8.9 mg C m −3 ) was comparable to one reported for filamentous fungi with assigned ecological importance. Our results show that unicellular fungi are an abundant and, based on high cellular ribosome content and fast dynamics, active part of coastal microbial communities. The known ecology of the visualized taxa and the observed dynamics suggest the existence of different ecological niches that link primary and secondary food chains, highlighting the importance of unicellular fungi in food web structures and carbon transfer.